Steering tjanpi in the digital desert. Issue 1 (1st March 2016) - Williams, Robyn
Tjanpi fibre-weaving is an innovative and performative art form, connected within the discourse that is contemporary Aboriginal art. Winning the 22nd National Aboriginal & Torres Strait Islander Art Award in 2005 for their large, woven 'Tjanpi Grass Toyota' positioned Papulankutja artists as experimental and creative with a distinct and quirky style. This article explores the relevance of cars in the Western Desert community of Papulankutja, which underpins the artists' ideas and values behind designing the artwork. It also advances new ideas and techniques within Indigenous art in the areas of fibre arts and sculpture. By presenting cars in contemporary art as an example of the engagement in the culture and consumption of material objects, and by comparing Papulankutja's 'Tjanpi Grass Toyota' with other recent examples of cars in contemporary art, I will illustrate how its successful entry in the contemporary art field positions it as innovative and creative, investing in new forms, genres and materials, and acting as an agent of transformation. In Papulankutja, cars, and in particular Toyotas, are not simply utilitarian vehicles but are inscribed in the social fabric of the community as symbolic meaning, and where the status of car ownership is highly sought.